Tailoring Photophysical Processes of Er3+‐Doped Gd3Ga5O12 Garnets for Enhanced Photoluminescence via Al3+ Ion Preference Substitution - Zhengjie Tian; Haiyan Wang; Yunfeng Lou; Qihang Deng; Zhi Yang; Xiyong Chen; Bingsuo Zou; Mingjian Yuan; Ruosheng Zeng (Carbon Energy, 2025)
ABSTRACT Rare‐earth ion‐doped garnets with excellent luminescent properties show great potential for temperature sensing, displays, and nondestructive detection. However, their limited luminescent modes and low photoluminescence quantum yields (PLQY) restrict further applications. In this study, we synthesized Al3+, Er3+‐co‐doped Gd3Ga5O12 garnets with multimode luminescence via a high‐temperature solid‐state method. Notably, the preferential substitution of Al3+ ion at octahedral‐coordinated GaI sites significantly enhanced the charge density and electron transition probability, achieving a PLQY enhancement of the down‐shifting luminescence from 35.1% to 68.5%. Al3+ ion also influences electron relaxation during up‐conversion luminescence, resulting in a color shift from red to yellow to green. Additionally, Al3+ incorporation increased the photoelectric conversion efficiency of light‐emitting diodes from 2.9% to 6.3% and improved temperature sensing sensitivity from 2.7% to 5.1% K⁻¹. This work provides new insights into the photophysical mechanisms and underscores the key role of Al3+ ion in optimizing the optical properties of garnet‐based materials.